Increased FT3/FT4 ratio in a certain range is associated with decreased glycemic variability in patients with type 2 diabetes - Ying Li; Tianrong Pan; Lingyu Wang; Yue Wang; Yu Gong; Guojuan Wang; Qianqian Zhang (Scientific Reports)
Abstract Thyroid hormone (TH) plays a crucial role in regulating glucose metabolism. However, the potential impact of the FT3/FT4 ratio, which reflects peripheral sensitivity to thyroid hormones, on glycemic variability in patients with type 2 diabetes (T2DM), has not been previously reported. To investigate the correlation between the FT3/FT4 ratio and glycemic variability in individuals with T2DM. In this retrospective analysis, a total of 468 inpatients with T2DM underwent continuous glucose monitoring (CGM) systems for a period of 6–14 days. Baseline clinical characteristics, laboratory tests, and CGM parameters were documented to investigate the correlation between FT3/FT4 ratio and CGM parameters. The levels of HBA, MG, SD, CV, LAGE, MODD and TAR2Scale were all higher in FT3/FT4Q1 compared with FT3/FT4Q2, FT3/FT4Q3 and FT3/FT4Q4 (all P < 0.01). Additionally, TIR was lower in FT3/FT4Q1 compared with the other quartiles (P < 0.01). Smooth curve fitting and saturation effect analysis revealed that there are curve-like relationships between the FT3/FT4 ratio and SD, MAGE, MODD and TAR2Scale. The inflection points of the fitted curves were found to be at FT3/FT4 = 0.279, 0.237, 0.253 and 0.282 respectively (all P < 0.05). Prior to the inflection point, the FT3/FT4 ratio was negatively related to SD, MAGE, MODD and TAR2Scale (all P < 0.05). Furthermore, The FT3/FT4 ratio exhibits a negative linear correlation with HBA and MG, while demonstrating a positive linear relationship with TIR (all P < 0.05). Binary logistic regression demonstrated that the FT3/FT4 ratio was independently related to HBA (P = 0.001), MG (P = 0.01), TAR2Scale (P = 0.003), LAGE (P = 0.014) and MAGE (P < 0.001). The increased FT3/FT4 ratio within a certain range (FT3/FT4 ≤ 0.282) is associated with decreased blood glucose variability and increased TIR. The FT3/FT4 ratio may act as a potential independent protective factor for glycemic fluctuation and glycemic control in patients with T2DM when it increases within a specific range.